2001
DOI: 10.1042/0264-6021:3530503
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-induced prostacyclin production is mediated by a protein kinase C (PKC)-dependent activation of extracellular signal-regulated protein kinases 1 and 2 involving PKC-δ and by mobilization of intracellular Ca2+

Abstract: We reported previously that vascular endothelial growth factor (VEGF) stimulates prostacyclin (PGI(2)) production via activation of the extracellular signal-regulated kinase (ERK) cascade. In this paper, we examined the role of protein kinase C (PKC) in this pathway. VEGF-induced PGI(2) generation and arachidonic acid release in human umbilical vein endothelial cells were inhibited by the PKC inhibitors GF109203X and calphostin C. VEGF increased PKC activity and immunoreactivity of the PKCdelta, alpha and epsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 48 publications
4
26
0
Order By: Relevance
“…These results are consistent with previous studies that L-NAME does not affect VEGF-induced ERK activity [51,54]. However, the mechanisms for the observed response to eNOS inhibition in the presence of EF are not clear and will be the subject of our future work.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous studies that L-NAME does not affect VEGF-induced ERK activity [51,54]. However, the mechanisms for the observed response to eNOS inhibition in the presence of EF are not clear and will be the subject of our future work.…”
Section: Discussionsupporting
confidence: 92%
“…induced hyperpermeability but failed to block VEGFinduced ERK-1/2 phosphorylation in HUVEC. Although this observation is in contrast to previous findings using porcine coronary venular endothelial cells (30), it is concordant with studies in HUVEC (16). Our results suggest that NO does not modulate VEGFinduced ERK-1/2 phosphorylation.…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with this, studies on platelets and endothelial cells have shown that this membrane relocation is consistent with an increased PLA 2 activity in membrane fractions [11,12]. Several studies have also shown that cPLA 2 ‐α activity in endothelial cells is regulated by phosphorylation [13–15], however the role of these modifications in the translocation and membrane association of cPLA 2 ‐α is unclear.…”
mentioning
confidence: 57%